Sosialiasi Mengenai Masa Tua yang Sehat dengan Mengenal Manfaat Teh Bunga Telang untuk Tubuh pada Masyarakat Desa Sojomerto - Elsa Sabina Putri Latifah; Nuralisah Meiliani Putri; Millatul Azizah; Mita Agustia; Fatma Nur Himatul Aliyah; Nahnu Robid Jiwandono (Jurnal Pelayanan Masyarakat, 2024)
The decline in physical and mental abilities is an inevitable sign of the aging phase. Maintaining health in old age involves not only physical activity and a balanced diet but also utilizing natural ingredients that can support overall body health. One such natural ingredient with significant potential to support health in old age is butterfly pea flower (Clitoria ternatea), known for its numerous health benefits, including stress reduction and cognitive function support. To raise awareness of the importance of preparing for healthy aging, the KKN MIT-18 Posko 57 Sojomerto Village team organized a seminar and workshop titled "Towards Healthy Aging and Knowing the Benefits of Butterfly Pea Flower." This event involved PKK cadres from Sojomerto Village and aimed to educate the community about the benefits of butterfly pea tea. The results of this activity showed an increased understanding among the community regarding the importance of maintaining physical and mental health in old age, as well as their enthusiasm for utilizing butterfly pea flower as a natural solution to support their health.